Copper Deficiency Induced Emphysema Is Associated with Focal Adhesion Kinase Inactivation - Mizuno, Shiro; Yasuo, Masanori; Bogaard, Harm J.; Kraskauskas, Donatas; Alhussaini, Aysar; Gomez-Arroyo, Jose; Farkas, Daniela; Farkas, Laszlo; Voelkel, Norbert F. (PLOS ONE, 2012)
Background Copper is an important regulator of hypoxia inducible factor 1 alpha (HIF-1α) dependent vascular endothelial growth factor (VEGF) expression, and is also required for the activity of lysyl oxidase (LOX) to effect matrix protein cross-linking. Cell detachment from the extracellular matrix can induce apoptosis (anoikis) via inactivation of focal adhesion kinase (FAK). Methodology To examine the molecular mechanisms whereby copper depletion causes the destruction of the normal alveolar architecture via anoikis, Male Sprague-Dawley rats were fed a copper deficient diet for 6 weeks while being treated with the copper chelator, tetrathiomolybdate. Other groups of rats were treated with the inhibitor of auto-phosphorylation of FAK, 1,2,4,5-benzenetetraamine tetrahydrochloride (1,2,4,5-BT) or FAK small interfering RNA (siRNA). Principal Findings Copper depletion caused emphysematous changes, decreased HIF-1α activity, and downregulated VEGF expression in the rat lungs. Cleaved caspase-3, caspase-8 and Bcl-2 interacting mediator of cell death (Bim) expression was increased, and the phosphorylation of FAK was decreased in copper depleted rat lungs. Administration of 1,2,4,5-BT and FAK siRNA caused emphysematous lung destruction associated with increased expression of cleaved capase-3, caspase-8 and Bim. Conclusions These data indicate that copper-dependent mechanisms contribute to the pathogenesis of emphysema, which may be associated with decreased HIF-1α and FAK activity in the lung.